Structural Volatility in Argentina: A Policy Report - Ricardo J. Caballero (Inter-American Development Bank, Research Department, 2000)
The author identifies sources of volatility in Argentina that include weak international financial links, a recurrent credit crunch and financial underdevelopment problem, a fragile fiscal situation, and a pervasive profit and collateral squeeze mechanism brought about by a rigid labor market and exchange rate system. The paper`s policy recommendations include improving external financial links, continuing and accelerating the path of domestic financial deepening, giving very high priority to the reduction of the public debt burden problem, and addressing the fundamental incompatibility between labor market rigidities and a highly inflexible exchange rate system.
Keywords: 330; Volatilität; Nationaleinkommen; Bruttoinlandsprodukt; Erwerbstätigkeit; Kapitalimport; Kreditmarkt; Öffentliche Schulden; Verdrängungseffekt; Arbeitsmarkt; Wechselkurssystem; Argentinien